PENGARUH POLITICAL MARKETING MIX TERHADAP KEPUTUSAN MEMILIH PARTAI GERINDRA DI KOTA SEMARANG - Zulkifli -; Joko Santoso (KH. A. Wahab Hasbullah University, 2018)
This study aimed to analyze the effect of the marketing mix (marketing mix) against the decision of choosing the party Gerindra in Semarang. This study uses as many as 108 respondents. Methods of analysis of this study using multiple linear regression, test the accuracy of measuring instruments used to test the validity, whereas to measure the extent to which the results of a measurement can be trusted, used the reliability test. In the classic assumption test, regression model multicoloniarity free, does not occur heteroskedastisitas, berditribusi normal and free from autocorrelation. Diproleh research results that the marketing mix (marketing mix) Positive Impact on the decision to choose, other results showed that the most influential variable in this study is the promotion while the most influential variable is the people. Keywords: Marketing Mix, Decision Choosing.